Preserving culture in education: Learning Media Innovation for Building Spaces Based on Temple Architecture - Maulida, Bella; Restian, Arina; Aini, Dian Fitri Nur (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The ability of fifth-grade students at SDN Penataran 06 to understand the concept of building space is still low, despite the importance of this material in the field of geometry, especially in everyday life. This study aims to develop local wisdom-based learning media with a theme centered on building space, inspired by the unique features of Penataran Temple. The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Based on questionnaire results, 98% of students reported an increase in their understanding of the learning material when the media was used effectively. Furthermore, 92% of educators acknowledged that the use of this media encouraged increased active participation from students in the classroom. This research demonstrates that local wisdom-based learning media can serve as an effective alternative in enhancing the quality of mathematics education in elementary schools.